PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN RUBRIK PENILAIAN MELALUI PEMBINAAN TERSTRUKTUR: (Penelitian Tindakan di SDN 1 Cempaka Lampung Utara) - Ernawati Ernawati (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2020)
One of the important tasks of the teacher is conducting research. The research developed at this time is the Class Research Model. But the reality on the ground, the assessment of learning outcomes is still very poorly adjusted. This is due to research conducted by teachers currently not using the assessment rubric. Therefore, it is necessary to have an effort to improve teacher competency in compiling assessment rubrics so that research meets the expected requirements. The problem in this study is how to improve the competence of teachers in grades IV, V, VI teaching Indonesian North Lampung in compiling assessment rubrics. To improve teacher competency in compiling the rubric of assessment, there needs to be structured coaching. Structured coaching is coaching that is carried out in a planned and ongoing manner, this research is a school action research. In this action research using repetitive cycles. Each cycle there are four stages, namely planning, implementing action, observation-evaluation, and reflection. The results showed that increasing teacher competency in compiling assessment rubrics could be improved through structured coaching. Structured guidance referred to in this study, is guidance (MGMP/KKG) activities. Based on the results of observations and evaluations of the cycle, it can be obtained that the assessment rubric prepared by the teacher is increasing. This is indicated by the average value of the results of the assessment rubric.